Ethnic Fission and Fusion in Biblical Genealogies - McEntire, Mark Harold (Journal of Biblical literature, 2021)
This article suggests that biblical genealogies are an important source for the way that ancients viewed and negotiated ethnic identity. Over and against a primordialist or constructivist view, a more flexible definition of ethnicity offers a stronger starting point for examining the genealogical genre. Ethnicity is a fluid discourse—a way of speaking to, from, and within individual and group differences in constant flux and under constant negotiation—mediated by claims of putative shared ancestral heritage. Our central claim is that biblical genealogies exhibit a strategic negotiation of identity that moves between two poles of ethnic fission and ethnic fusion. The evidence we examine in the first section suggests that there are numerous occasions when Israelites by biological birth were deliberately excluded from the genealogy. Furthermore, as the second section demonstrates, there are compelling cases when non-Israelite foreigners were included in spite of their differences. According to our analysis, the concept of ethnic fission and fusion explains how genealogies functioned to define ethnic boundaries at key moments in Israel's history.